Community and infrastructure preparedness towards the implementation of sister village disaster mitigation program - Rivani, Rivani; Mei, E. T. W. (2022)
As one of the most active volcanoes in Indonesia, Merapi Volcano has potential risk towards the inhabitants living nearby. After the 2010 paroxysmal eruption, Sister Village program was established in Magelang Regency as an alternative strategy to a better disaster management by evacuating people living in the highest volcanic disaster-prone area (affected villages) to safer zones (buffer villages). By taking location in Tamanagung Village, Muntilan Sub-district, Magelang Regency as buffer village, this research tries to understand how the Sister Village program is implemented in this area, specifically to understand community and infrastructure preparedness. The study used both quantitative and qualitative data taken directly in the field by using questionnaires towards 40 respondents, checklists, and interview with keypersons. Community preparedness were analyzed using four parameters: knowledge, policy and guideline, emergency response plan and resource mobilization. The results showed that among four parameters, only knowledge parameter showing a good preparedness, while the four others still need to be improved. The use of information technology by the public, such as Whatsapp application, is widely growing. In terms of infrastructure preparedness in the buffer village, some enhancements in terms of capacity, infrastructure safety, health aspects, and comfort are still necessary.